Efficacy of Insecticides against Fall Armyworm, Spodoptera frugiperda (J.E. Smith) in Maize Field in Chitwan, Nepal - Bhandari, Ghana Shyam; Bhandari, Priyanka; Sah, Lalit (Journal of Nepal Agricultural Research Council, 2024)
A field experiments were conducted to determine the comparative efficacy of different chemical insecticides against the fall armyworm, Spodoptera frugiperda (J.E. Smith), in maize under natural field conditions during winter seasons of 2020 and 2021. The experiments were laid out in a randomized complete block design with four replications and seven treatments, namely: chlorantraniliprole 18.5% SC @ 0.4 ml/liter of water; azadirachtin 1500 ppm @ 5 ml/liter of water; spinosad 45% SC @ 0.3 ml/liter of water; spinetoram 11.7% SC @ 0.4 ml/liter of water; novaluron 10% EC @ 2 ml/liter of water; emamectin benzoate 5% SG @ 0.4 g/liter of water; and an untreated control at National Maize Research Program (NMRP), Chitwan, Nepal. The efficacy study revealed that all the treatments significantly reduced plant damage and increased grain yield compared to the untreated control (p < 0.05). Spinosad proved to be the most effective, with a minimum infestation rate of 9.3% followed by chlorantraniliprole (12.4%) and spinetoram (16.5%), compared to the untreated control (79.6%). Spinosad treated plot also yielded the highest grain 4885 kg/ha, followed by spinetoram (4647 kg/ha), chlorantraniliprole (4470 kg/ha) and emamectin benzoate (4335 kg/ha) as compared to the untreated control (1758 kg/ha) in the combined analysis. Although azadirachtin 1500 ppm was the least effective among the treatments, it was still significantly superior to the untreated control. Furthermore, plant height, ear height, cob length, cob diameter, thousand grain weight and grain yield of maize were negatively correlated with foliar damage done by fall armyworm.